Optimalisasi Platform Merdeka Mengajar (PMM) Untuk Mewujudkan Kurikulum Merdeka di SMP Negeri 1 Bangli - Cahya Purnama, Sang Putu Gede; Suyanta, I Wayan (Metta : Jurnal Ilmu Multidisiplin, 2025)
The government is trying to improve the quality of education by launching the Merdeka curriculum in order to transform learning that liberates learning for teachers and students. In its implementation, the government created the Merdeka Teaching platform as a reference for principals and teachers to implement the Merdeka Curriculum in schools. The purpose of this study was to determine the strategy, impact and obstacles to optimizing the Merdeka Teaching Platform (PMM) to realize the implementation of the Merdeka Curriculum. This study was conducted using qualitative research based on a descriptive naturalistic approach with data collection techniques through observation, interviews, and document analysis. The results of the study showed strategies to optimize the use of the Merdeka Teaching Platform at SMP Negeri 1 Bangli such as habituation of platform use, formation of learning communities, implementing focus group discussions (FGD), the impact of optimizing the Merdeka Teaching platform is increasing teacher competence, developing learning innovations, increasing the development of learning resources and teachers are able to work and share good practices. Several obstacles in the application of the Merdeka Teaching Platform such as slow adaptation of technology, increasing teacher burden, limited access to technology and low teacher awareness.